2021
DOI: 10.1248/bpb.b21-00017
|View full text |Cite
|
Sign up to set email alerts
|

Free-Radical Scavenger NSP-116 Protects the Corneal Epithelium against UV-A and Blue LED Light Exposure

Abstract: The corneal epithelium is continuously exposed to oxygen, light, and environmental substances. Excessive exposure to those stresses is thought to be a risk factor for eye diseases. Photokeratitis is damage to the corneal epithelium resulting in a painful eye condition caused by unprotected exposure to UV rays, usually from sunlight, and is often found in people who spend a long time outdoors. In modern life, human eyes are exposed to artificial light from light-emitting diode (LED) displays of computers and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…IL-6, ROS, NF-κB, and UV are closely related, and UV irradiation can easily occur in the eye. It has been reported that UV-A exposure induces mitochondrial damage, ROS production, and NF-κB activation in HCE-T, and decreases the cell barrier function [32,33]. In addition, Benko et al demonstrated that UV exposure increases IL-6 production [34].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6, ROS, NF-κB, and UV are closely related, and UV irradiation can easily occur in the eye. It has been reported that UV-A exposure induces mitochondrial damage, ROS production, and NF-κB activation in HCE-T, and decreases the cell barrier function [32,33]. In addition, Benko et al demonstrated that UV exposure increases IL-6 production [34].…”
Section: Discussionmentioning
confidence: 99%
“…Cell death analyses were performed as described previously [ 11 , 12 ]. In brief, Hoechst 33342 and PI (Thermo Fisher Scientific) were added to the cell cultures at the final concentration of 8.1 µM and 1.5 µM, respectively, followed by an additional incubation at 37 °C for 15 min.…”
Section: Methodsmentioning
confidence: 99%